The numbers behind success: key metrics for advancing in male EURO 2024 - Martín-Castellanos, Adrián; Pereira-Monteiro, Marcos Raphael; Hermosilla-Perona, Francisco; Barba-Ruíz, Manuel; Solana, Diego Muriarte; Alonso-Pérez-Chao, Enrique (Frontiers in Sports and Active Living, 2025)
This study aimed to identify the key performance indicators (KPIs) that distinguish football teams advancing through the group and knockout stages in the UEFA EURO 2024 tournament. A total of 51 matches were analyzed, including 66 variables sourced from official UEFA statistics. Principal Component Analysis (PCA) was applied to reduce the dataset, retaining variables with eigenvalues greater than 1 and factor loadings of at least 0.6, resulting in a final selection of 37 KPIs. These variables were grouped into five categories: distribution, attacking, defending, goalkeeping, and disciplinary. Generalized linear models were used to compare team performance based on progression status in each phase. In the group stage, advancing teams showed significantly better performance in variables such as Goals Conceded and Passes Completed Backward. In the knockout stage, new decisive KPIs emerged, including Pass Accuracy, Goals Scored Inside the Penalty Area, Assists, Solo Runs Into Key Play Area, and Tackles. Effect sizes for variables like Ball Possession, Attacks, and Goalkeeping metrics increased, highlighting their growing influence. Overall, effective distribution, minimal goals conceded, and offensive effectiveness were critical for progression. While discipline was relevant during the group stage, its importance diminished in the knockout rounds. These results provide practical implications for coaches and analysts, emphasizing the importance of strategic flexibility and data-driven preparation throughout different stages of tournament play.